Pengaruh Promosi Cashback Pada Shopee Dan Harga Terhadap Perilaku Konsumen - Volyn Visya Handini; Nur Fadhila Maulana Akhyar; Lulu Lusy Irawati; Nadya Lailatunnajwa; Arifudin Arifudin (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
This article aims to understand whether cashback and price promotions can influence consumer behavior centered on students of the Sharia Economics Study Program, Faculty of Economics and Islamic Business, UIN Siber Syekh Nurjati Cirebon. This issue is focused on whether there is a change in the behavior of consumers who make purchases using Shopee. The cashback referred to in this study is a form of Shopee coins which can then be used to repurchase clothing products, household appliances, order food and other needs. The form of research used is associative quantitative research. The sample in this study were students of the Faculty of Economics and Islamic Business UIN Sheikh Nurjati Cirebon Sharia Economics Study Program. The sample in this study amounted to 70 respondents. The data was collected through distributing questionnaires which were then processed with multiple regression analysis techniques using the IBM SPSS Statictics 25 application. This study concludes that based on the results of the hypothesis test, the Cashback promotion variable has a positive and significant effect at a value of 3.535 on consumer behavior and the Price variable has a positive and significant effect at a value of 6.515 on consumer behavior. The simultaneous test shows that cashback promotion and price have a positive and significant effect with an fcount value of 45.569 and the test value of the coefficient of determination on the independent variable of 57.7% on the dependent variable. With the regression equation obtained 5.451 + 0.268X1 + 0.461X2.